Crocin Bleaching Assay Using Purified Di-gentiobiosyl Crocin (-crocin) from Iranian Saffron - Bathaie, Seyedeh Zahra (Mashhad University of Medical Sciences, 2011)
OBJECTIVE(S): Crocin bleaching assay (CBA) is a new method for determination of antioxidant capacity. In CBA, addition of hydrogen to the conjugated double bonds of crocin results in reduction of crocin and increase in the absorbance at 440 nm, which is considered as a measure of antioxidant potential. Here CBA method was set up using di-gentiobiosyl crocin or α-crocin from Iranian saffron. Then, the antioxidant activity of some known antioxidants i.e. L-ascorbic acid, bilirubin, Trolox, uric acid, and some plasma samples of infants, were tested. The results were compared to that obtained by ferric reducing antioxidant power" (FRAP) as a standard method. MATERIALS AND METHODS: Di-gentiobiosyl crocin was extracted and purified from Iranian saffron as previously described by us. Then, the CBA procedure using α-crocin was done in 2 different aquatic conditions, >50% or >90% of water. Results were analyzed by both the Bors method (calculating the relative rate constants= K(rel)) and the Tsimidou method (calculating the percent of -crocin bleaching inhibition=% Inh). RESULTS: Our results indicated the following order of antioxidant potential for the above mentioned agents: ascorbic acid > uric acid > Trolox. However, these results are very similar to the data reported by others, but they are strongly related to the aqueous condition. In addition, uric acid showed different properties at different concentrations; so that it showed the antioxidant activity at low concentrations but it acted as a prooxidant at higher concentrations. Bilirubin interfered with this test, possibly because its maximum absorbance is close to the crocin. The obtained data for the antioxidant capacity of the serums was comparable with FRAP assay, except for the sample that contains high bilirubin concentration. CONCLUSION: In conclusion, it seems that CBA using the main fraction of crocin (-crocin) is a simple and useful method for determination of antioxidant potential of aqueous samples. In addition, the CBA ability to distinguish the samples that contain bilirubin or high uric acid content is helpful in clinical laboratories.